Chondrogenic phenotype of different cells encapsulated in κ-carrageenan hydrogels for cartilage regeneration strategies - Popa, Elena Geta (2012)
Engineering articular cartilage substitutes using hydrogels with encapsulated cells is an approach that has received increasing attention in recent years. Hydrogels based on κ-carrageenan (κC), a thermoreversible natural-origin polymer, have been recently proposed as new cell/growth factor delivery vehicles for regenerative medicine. In this work, we report the potential of such hydrogels encapsulating either human-adipose-derived stem cells (hASCs), human nasal chondrocytes (hNCs), or a chondrocytic cell line (ATDC5) for cartilage regeneration strategies. The in vitro cellular behavior of the encapsulated cells within κC hydrogel was analyzed after different culturing periods using biochemical assays and histological and real-time reverse-transcription PCR analysis. The three types of cells encapsulated in κC hydrogels showed good cellular viability and proliferation up to 21 days of culture, and the cell-laden hydrogels were positive for specific cartilage markers. In summary, the results demonstrate that hASCs embedded in κC hydrogels proliferate faster and exhibit higher expression levels of typical cartilage markers as compared with hNCs or ATDC5 cells. Based on these data, it is possible to conclude that κC hydrogel provides a good support for culture and differentiation of encapsulated cells and that hASCs may provide an advantageous alternative to primary chondrocytes, currently used in clinical treatments of cartilage defects/diseases.